2020
DOI: 10.1140/epjh/e2020-10027-6
|View full text |Cite
|
Sign up to set email alerts
|

Rudolf Ladenburg and the first quantum interpretation of optical dispersion

Abstract: In 1921, the experimental physicist Rudolf Ladenburg put forward the first quantum interpretation of optical dispersion. Theoretical physicists had tried to explain dispersion from the point of view of quantum theory ever since 1913, when Niels Bohr proposed his quantum model of atom. Yet, their theories proved unsuccessful. It was Ladenburg who gave a breakthrough step toward our quantum understanding of dispersion. In order to understand Ladenburg’s step, I analyze Ladenburg’s experimental work on dispersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…When Bohr introduced his theory of electron orbitals he immediately recognized the possibility that the discrete lines of atomic spectra are related to the discrete lines in dispersion phenomena [3]. Other researchers, in particular Debye and Sommerfeld, were also inspired by that possibility and a series of papers appeared that tried to explain the discrete and continuous properties of dispersion by introducing classically inspired modifications of the electron orbitals [2,4,5]. However, when experiments revealed that the characteristic frequencies of anomalous dispersion coincide with the frequencies of the spectral lines it was evident that orbiting electrons could not account for both and a complete break from classical theory was necessary.…”
Section: Matrix Mechanics 21 Historical Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…When Bohr introduced his theory of electron orbitals he immediately recognized the possibility that the discrete lines of atomic spectra are related to the discrete lines in dispersion phenomena [3]. Other researchers, in particular Debye and Sommerfeld, were also inspired by that possibility and a series of papers appeared that tried to explain the discrete and continuous properties of dispersion by introducing classically inspired modifications of the electron orbitals [2,4,5]. However, when experiments revealed that the characteristic frequencies of anomalous dispersion coincide with the frequencies of the spectral lines it was evident that orbiting electrons could not account for both and a complete break from classical theory was necessary.…”
Section: Matrix Mechanics 21 Historical Perspectivesmentioning
confidence: 99%
“…However, when experiments revealed that the characteristic frequencies of anomalous dispersion coincide with the frequencies of the spectral lines it was evident that orbiting electrons could not account for both and a complete break from classical theory was necessary. Ladenburg was the first to suggest how the new quantum theory would appear by following Einstein's reasoning leading to the A and B coefficients [5][6][7]. This enabled him to equate two theoretical expressions, the energy absorbed/emitted by N classical resonators and the energy absorbed/emitted by N 0 quantum atoms.…”
Section: Matrix Mechanics 21 Historical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…He drowned in a sailboat accident on Lake Müggel. [35][36] His third son, Rudolf, became a German-American atomic physicist. 37 In 1905, he has had to undergo amputation of the right leg.…”
Section: The Important Events In the Ladenburg's Lifementioning
confidence: 99%